Effect of specific training on swimming start performance - De La Fuente, B.; Arellano, R. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: The swimming start is a significant performance component for success in competitive swimming, especially in short events. The purpose of the study was to determine how the swimmers start improvement could be related to a specific training providing accurate information about the start duration at different distances (10 and 15m). METHODS: Differences between manual timing and times obtained through video analysis were previously set. Results highlighted the importance of an accurate evaluation. The system developed allowed swimmers and coaches to know the starting times as they know in competitions. The system consisted in an electronic touchpad placed on the pool`s lateral lane. A group (n=42) of regional swimmers and P. E. students participated on the study. The group was divided equally into experimental and control groups. Each group practiced during 10 sessions. The experimental group (EG) received accurate information about their starting times (Terminal Knowledge of Results [TKR]). Meanwhile, control group (CG) did not receive any information after each trial. RESULTS: We did not find statistical differences in start times measured at 10 and 15m, between groups. Nevertheless, both groups significantly improved their starting times. However, greater improvements were produced within the EG (more than 5% vs less than 2% at the CG). To check the significance of the improvement within each group, a related samples t-Test was performed. Results showed greater significance levels in the EG than in the CG (p<0.001 vs p<0.005). In addition, when an individual intra-subject analysis was applied, performance tended to be more consistent within the EG (differences between best trial and average time were reduced up to 0.05s in some subjects). DISCUSSION: Due to the short start times, accurate evaluation must be performed, to avoid false improvements due to erroneous measurements. Results suggested that the systematic and controlled repetition of the swimming starts, leads to performance improvement. This should be taken into account to increase the start practicing time within a whole year`s planning. In addition giving the swimmers accurate KR produces greater performance improvements than only systematic repetition with manual timing (not accurate enough). Moreover, the system seems to be individually more effective, making the start performance more consistent. This is important when considering the anticipated performance at important competitions.